A Unified Approach to the Elastic Lateral Buckling of Beams - Nethercot, David A.; Rockey, K.C. (Engineering Journal, 1972)
The lateral buckling of beams is a complicated phenomenon, the maximum elastic bending stress necessary to cause buckling being dependent upon the geometrical and material properties of the beam, the type and position of the loading, and also the support conditions. This paper presents a design procedure which enables all of these factors to be allowed for, in an accurate yet simple and direct manner, for 41 different cases of loading and support. The proposed method is both more accurate and more versatile than existing methods used in design codes.